(untitled) (Construction Economics and Building, 2026)
Improving the energy efficiency of buildings has become a critical priority, particularly in hot–humid climates where cooling demands are exceptionally high. Hence, due to buildings being considered one of the biggest contributors to energy consumption, utilizing feasible retrofitting strategies is critical. This study assessed the impact of three retrofitting strategies—enhanced glazing, enhanced roof insulation, and reflective cooling paint on exterior walls—on the cooling load, energy consumption, and economic feasibility of a residential townhouse in hot–humid climates in Sharjah. The methodology involved simulating various retrofitting scenarios using DesignBuilder to assess their impact on energy consumption and cooling load, followed by an economic analysis to evaluate feasibility in terms of cost, energy savings, and payback periods. It was found that using reflective paint achieved the highest reductions in energy consumption (8%) and cooling load (13%), while combining reflective paint with glazing upgrades offered up to 10% energy savings and 16% cooling load reduction. These results highlight that reflective paints and their combinations with other strategies provide a cost-effective and energy-efficient solution for retrofitting older buildings in hot–humid climates, making them a sustainable choice for reducing energy demand and promoting thermal comfort. The findings offer practical insights for replicable interventions in similar hot–humid urban contexts and contribute to the regional transition toward nearly net-zero energy buildings.